Minsky's Analysis of Financial Capitalism - Dimitri B. Papadimitriou; L. Randall Wray (Levy Economics Institute of Bard College, 1999)
In this paper, the authors discuss Minsky's analysis of the evolution of one variety of capitalism–financial capitalism–which developed at the end of the nineteenth century and was the dominant form of capitalism in the developed countries after World War II. Minsky's approach, like those of Schumpeter and Veblen, emphasized the importance of market power in this stage of capitalism. According to Minsky, modern capitalism requires expensive and long-lived capital assets, which, in turn, necessitate financing of positions in these assets as well as market power in order to gain access to financial markets. It is the relation between finance and investment that creates instability in the modern capitalist economy. Financial capitalism emerged from World War II with an array of new institutions that made it stronger than ever before. As the economy evolved, it moved from this more successful form of financial capitalism to the fragile form of capitalism that exists today.
Keywords: 330